2021
DOI: 10.1155/2021/1439563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Stem Cell Therapy in Ovariectomized Osteoporotic Rats Based on Micro-CT and Dual-Energy X-Ray Absorptiometry: A Systematic Review and Meta-Analysis

Abstract: Objective. Osteoporosis is an abnormal bone metabolism disease characterized by microstructural degeneration of bone tissue and reduction in bone mass, resulting in increased brittleness of bone tissue and susceptibility to fracture. Due to the tissue regenerative potential of stem cell transplantation, it is now used in the treatment of various disease models such as osteoporosis. The purpose of this work is to carry out a systematic review and meta-analysis of the efficacy of stem cell therapy in ovariectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Wu et al found differentially expressed circRNAs in patients with osteoporosis and found that 237 circRNAs were upregulated and 279 circRNAs were down-regulated, which also confirmed the important role of circRNAs in the osteogenic differentiation of BMSCs [9] . Another study found that circRNAs were differentially expressed in patients with traumatic femoral head necrosis, and found that 234 circRNAs were upregulated and 148 circRNAs were downregulated [10] . Zou et al found that circRNAs such as circ_28313, circ_0016624, circ_0006393, circ_0076906, and circ_0048211 were differentially expressed in patients with osteoporosis and played an important role in the differentiation, proliferation, and apoptosis of bone marrow mesenchymal stem cells [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found differentially expressed circRNAs in patients with osteoporosis and found that 237 circRNAs were upregulated and 279 circRNAs were down-regulated, which also confirmed the important role of circRNAs in the osteogenic differentiation of BMSCs [9] . Another study found that circRNAs were differentially expressed in patients with traumatic femoral head necrosis, and found that 234 circRNAs were upregulated and 148 circRNAs were downregulated [10] . Zou et al found that circRNAs such as circ_28313, circ_0016624, circ_0006393, circ_0076906, and circ_0048211 were differentially expressed in patients with osteoporosis and played an important role in the differentiation, proliferation, and apoptosis of bone marrow mesenchymal stem cells [3] .…”
Section: Discussionmentioning
confidence: 99%
“…and Uejima et al . injected MSCs into the marrow cavity and assessed the physical property through biomechanical tests, and they showed MSCs contributed to the maintenance of biomechanical properties . The results demonstrated that the TNF-α levels were decreased, and the level of T cell apoptosis, bone volume fraction, trabecular number, and BMD increased after MSC injection.…”
Section: Introductionmentioning
confidence: 99%